Roxadustat effectiveness versus ESAs in peritoneal dialysis patients during the COVID-19 pandemic: A retrospective study - Jie Liu; Kefan Zhou; Chen Meng; Zhuzhu Liu; Ruihua Huang; Yousuf Waheed; Fan Yang; Kun Liu; Jiaqi Zhao; Lin Zhang; Xiaoyan Yu; Shuang Li; et al. (PLoS ONE, 2025)
Background The COVID-19 pandemic has made treating renal anemia in chronic kidney disease (CKD) patients undergoing peritoneal dialysis (PD) difficult. The current study aims to compare roxadustat with erythropoiesis-stimulating agents (ESAs) during the COVID-19 pandemic. Methods We conducted a single-center, retrospective study during the COVID-19 outbreak in China, from December 7, 2022, to January 31, 2023. The study involved patients undergoing PD who were divided based on the medication used to treat renal anemia; the roxadustat group (n = 34) and the ESAs group (n = 120). We analyzed the effectiveness of treating anemia, cost, medication adherence, and clinical outcomes related to COVID-19. Patients were followed up for 9 months. Results The baseline of hemoglobin levels was (110.03 ± 1.71 g/L in the roxadustat and 110.1 ± 1.52 g/L in the ESAs groups, respectively), after 9 months of inspections, the levels of hemoglobin were (121.26 ± 2.03 g/L in the roxadustat and 118.49 ± 1.35 g/L in the ESAs groups, respectively). The roxadustat subgroup analysis indicated that total cholesterol and low-density lipoprotein levels in the roxadustat group decreased from baseline in subjects not receiving statins (3.39 ± 0.12 vs. 4.2 ± 0.21 mmol/L and 2.21 ± 0.23 vs. 3.65 ± 0.37 mmol/L, P < 0.05). The Morisky score of the roxadustat group was higher [7 (5, 8) vs. 6 (4, 8), P < 0.01]. The drug cost of the roxadustat group was higher, but another additional cost for correcting anemia was significantly reduced. The infection rate of COVID-19 and the mortality rate caused by COVID-19 were lower in roxadustat group. Conclusion During the COVID-19 pandemic, both roxadustat and ESAs effectively improved renal anemia in PD patients, however, the roxadustat group experienced less additional costs for anemia correction and better medication compliance.